Supplementation of Kiwifruit Polyphenol Extract Attenuates High Fat Diet Induced Intestinal Barrier Damage and Inflammation via Reshaping Gut Microbiome - Yuan, Minlan; Chen, Xiao; Su, Tianxia; Zhou, Yan; Sun, Xiaohong (Frontiers in Nutrition, 2021)
BACKGROUND: Impaired intestinal integrity and barrier function is associated with various diseases, including inflammatory bowel disease and metabolic syndrome. In recent years, plant-derived polyphenols have attracted much attention on regulating intestinal barrier function. Kiwifruit was recorded as a traditional Chinese medicine which can treat gastrointestinal diseases, but the mechanism was still unclear. In this study we investigated the effects of kiwifruit polyphenol extracts (KPE) on high fat diet induced intestinal permeability and its possible mechanism. RESULTS: Dietary supplementation of KPE with 50 or 100 mg/kg bw could inhibit the increase of intestinal permeability caused by HFD and promote the expression of tight junction protein (Claudin-1, Occludin and ZO-1). From microbial diversity and RT-PCR, KPE administration reshaping gut microbiome, the relative abundance of Lactobacillus and Bifidobacterium were increased, and the relative abundance of Clostridium and Desulfovibrionaceae were decreased. The changes in microbe may influence intestinal inflammatory status. Then the expression of TLRs and cytokines were detected. KPE supplementation showed anti-inflammatory effect, the expression of IL-10 was increased and the expression of TLR-2, TLR-4, TNF-α and IL-1β were decreased. Correlation analysis indicated that the expression of tight junction protein was negative correlation with TLR-2, TLR-4, TNF-α and IL-1β expression, but positively correlated with Bacteroidete, Bifidobacterium and IL-10 expression; the expression of Bacteroidete, Lactobacillusand and Bifidobacterium were negative correlation with TLR4, TNF-α and IL-1β expresion. CONCLUSION: KPE treatment relieve the intestinal damage caused by HFD, which was related to the regulation of Bacteroidete, Lactobacillusand and Bifidobacterium expression and inhibit intestinal inflammation. KPE could be a functional component for preventing gut damage and its related disease.